Airpower over Gallipoli, 1915-1916 - Pavelec, Sterling Michael (History of military aviation, 2020)
"Sterling Michael Pavelec recounts the adventures of the handful of aviators and their aircraft during the Gallipoli Campaign. As the contest for the Dardanelles Straits and the Gallipoli Peninsula raged, three Allied seaplane tenders and three land-based squadrons flew and fought against two mixed German and Ottoman squadrons (one land-based, one seaplane) against each other, the elements, and the fledgling technology. The contest was marked by experimentation, bravado, and airborne carnage as the men and machines plied the air to gain a strategic advantage in the new medium."--